(Natlas ANATOMII ^ELOWEKA (B4 (NTOMs (Nu^EBNIKs - (Nr(B,(Nd(B,(NsINELXNIKOWs; (NsINELXNIKOW q(B.(Nrs; (NsINELXNIKOW a(B.(Nqs ((NmOSKWAs (NmEDICINAs, 2009)
(NwO WTOROM TOME RASSMATRIWA@TSQ U^ENIE O WNUTRENNOSTQH(B- (NPI]EWARITELXNOJ DYHATELBNOJ MO^EWOJ I POLOWYH SISTEMAH A TAKVE \NDOKRINNYE VELEZY s
Keywords: (Natlas ANATOMII ^ELOWEKA (B1 (NTOMs